Scoping Review: Behind the Scenes of Self-Disclosure in Users of Second Instagram Accounts - Lathifunnisa, Meyra Zahra; Firdasannah, Astri; Nurbadriah, Wida (Psychosocia : Journal of Applied Psychology and Social Psychology, 2025)
Instagram is one of the most popular social media platforms because it is an application where users can use digital filters and share photos and videos with other users. The emergence of second accounts among Instagram users has revived the fundamental human need to socialise with self-disclosure to those in their surroundings. This study aims to identify and explore the motives and factors that influence and are influenced by self-disclosure among second-account Instagram users. This study employs a scoping review methodology. The results of this study provide an overview of the motives and factors that influence and are influenced by self-disclosure among second-account Instagram users. The identified motives were following trends, fostering openness, and building friendships. The factors identified included openness, self-confidence, context, motivation, personality traits, culture, and dyadic effects.